Laser coulomb explosion imaging of molecular dynamics - Bocharova, Irina A. (Kansas State University, 2009)
The goal of this dissertation project was to study the dynamics of nuclear motion in diatomic (H[subscript]2, N[subscript]2, O[subscript]2, CO) and triatomic (CO[subscript]2) molecules initiated by the ionization and/or excitation of these molecules with near-IR few-cycle laser pulses. This dynamics includes vibrational and rotational motion on the electronic potential surfaces of the molecules and their molecular ions. The experimental techniques used included the pump-probe approach, laser Coulomb explosion imaging and the COLTRIMS technique. The results are presented in four chapters. A study of rotational and vibrational nuclear dynamics in H[subscript]2 and D[subscript]2 molecules and ions initiated by 8 fs near-IR pulses is presented in Chapter 4. Transient alignment of the neutral molecules was observed and simulated; rotational frequency components contributing to the rotational wavepacket dynamics were recovered. Chapter 5 is dedicated to revealing the contribution of excited dissociative states of D[subscript]2[superscript]+ ions to the process of fragmentation by electron recollision. It was shown that it is possible to isolate the process of resonant excitation and estimate the individual contributions of the [superscript]2sigma[subscript]u[superscript]+ and [superscript]2pi[subscript]u states. In Chapter 6 the subject of investigation is the nuclear dynamics of N[subscript]2, O[subscript]2 and CO molecules initiated by ionization of a neutral molecule by a short intense laser pulse. It was shown that the kinetic energy release of the Coulomb explosion fragments, measured as a function of the delay time between pump and probe pulses, reveals the behavior of nuclear wave packet evolution on electronic states of the molecular ions. It was shown that information on the dissociation and excitation pathways can be extracted from the experimental spectra and the relative contributions of particular electronic states can be estimated. Chapter 7 is focused on studying the fragmentation of CO[subscript]2 following the interaction of this molecule with the laser field. The most important result of this study was that it presented direct experimental evidence of charge-resonant enhanced ionization (CREI), a phenomenon well-studied for diatomic molecules and predicted theoretically for triatomic molecules. The critical internuclear distance, the relevant ionic charge state and a pair of charge-resonant states responsible for the CREI were also found.
Keywords: Coulomb explosion; Nuclear dynamics in laser fields; Physics, Atomic (0748); Physics, Molecular (0609)